Integrated emergy and economic evaluation of the dominant organic rice production systems in Jiangsu province, China - Gao, Pinglei; Wang, Haoyu; Sun, Guojun; Xu, Qiang; Dou, Zhi; Dong, Erjia; Wu, Wenge; Dai, Qigen (Frontiers in Plant Science, 2023)
Organic farming is considered a promising solution for reducing the environmental burdens related to agricultural production; for example, organic farming is believed to lower energy consumption and balance long-term productivity with ecological sustainability. In this study, the economic viability and environmental and sustainability performance of the four dominant organic production modes, namely, rice-green manure rotation (RG), rice-duck co-culture (RD), rice-crayfish co-culture (RCF) and rice monoculture (RM), were evaluated in Jiangsu Province, China. The RM mode was the most uneconomic organic rice production mode with the highest cost input and the lowest product output but had relatively higher sustainability due to the higher proportion of renewable resources to total emergy inputs. Compared with the RM mode, 54% and 58% of organic fertilizer and 50% and 45% of labor were decreased in the RD and RCF modes, respectively, and organic fertilizer decreased by 53% in the RG mode. The total cost was lower, but the value-to-cost ratio, economic benefit density and benefit-cost ratio were significantly higher in the RG, RD and RCF modes than in the RM mode. Although the RD and RCF modes had higher efficiency in converting resources to total nutrition density units and monetary value, they imposed higher environmental pressure with a lower renewable fraction and emergy sustainability index than those in the RM mode. The RG mode had higher emergy utilization efficiency and the highest renewable fraction and emergy sustainability index among the four organic rice production modes. Considering the ecological and economic effects, the RG mode was conducive to improving the economic viability and sustainability of organic rice production in Jiangsu Province. The large labor input is the primary factor limiting the development of rice-green manure rotation; therefore, efficient weed management providing significant reductions of labor costs should be developed to further promote rice-green manure rotation for organic rice production.